Pengaruh Lingkungan Sosial Terhadap Perilaku Penggunaan Rokok Elektrik (VAPE) Pada Siswa Di SMKN 5 Sidenreng Rappang - Fahria, Ummi; Said, Sunandar; Ramlan, Pratiwi (JUKEJ : Jurnal Kesehatan Jompa, 2025)
The use of electronic cigarettes (vapes) among students is influenced by the social environment, including the influence of family, peers, and the Smoke-Free School Policy. The family environment plays a significant role, where parental support or lack of supervision can affect student behavior. Peers also have a substantial impact, as students are often influenced by the habits or pressure from their peer groups. In addition, school policies that prohibit or restrict the use of cigarettes (vapes) also affect student behavior. These factors are interrelated and collectively influence students' decisions to smoke or use vapes.This study aims to determine the influence of the social environment on the behavior of electronic cigarette (vape) use among students at SMKN 5 Sidrap. This research falls into the category of quantitative research with a cross-sectional design. The sampling technique used was cluster random sampling, while the data collection techniques included questionnaires, observation, and interviews. The data analysis techniques used were univariate, bivariate, and regression analysis. The simple regression results of this study indicate an influence between the family and vape use behavior with a significance value of 0.015 (p < 0.05). Peers also have an influence on vape use behavior with a significance value of 0.030 (p < 0.05), and the smoke-free school policy influences vape use behavior with a significance value of 0.796 (p < 0.05).The conclusion of this study is that there is an influence between family, peers, and the smoke-free school policy on the behavior of vape use among students at SMKN 5 Sidenreng Rappang.